Surface Topography, Bacterial Carrying Capacity, and the Prospect of Microbiome Manipulation in the Sea Anemone Coral Model Aiptasia - Costa, Rúben M.; Cárdenas, Anny; Loussert-Fonta, Céline; Toullec, Gaëlle; Meibom, Anders; Voolstra, Christian R. (Frontiers in Microbiology, 2021)
Aiptasia is an emerging organism to study cnidarian symbioses due to its taxonomic relatedness to other anthozoans such as stony corals and similarities of its microalgal and bacterial partners, complementing the existing Hydra (Hydrozoa) and Nematostella (Anthozoa) model systems. Despite the availability of studies characterizing the microbiomes of several natural Aiptasia populations and laboratory strains, knowledge on basic information, such as surface topography, bacterial carrying capacity, or the prospect of microbiome transplants is lacking. Here we address these knowledge gaps. Our results show that the surface topographies of the model hydrozoan Hydra and anthozoans differ substantially, whereas the ultrastructural surface architecture of Aiptasia and stony corals is highly similar. Further, we determined a bacterial carrying capacity of ~104 and ~105 bacteria (i.e., colony forming units, CFUs) per polyp for aposymbiotic and symbiotic Aiptasia anemones, respectively, suggesting that the symbiotic status changes microbial association/density. Microbiome transplants from Acropora humilis and Porites sp. to gnotobiotic Aiptasia showed that only a few foreign bacterial taxa were effective colonizers. Our results shed light on the putative difficulties of transplanting microbiomes between cnidarians in a manner that consistently changes microbial host association at large. At the same time, our study provides an avenue to identify bacterial taxa that exhibit broad ability to colonize different hosts as a starting point for cross-species microbiome manipulation. Our work is relevant in the context of microbial therapy (probiotics) and microbiome manipulation in corals and answers to the need of having cnidarian model systems to test the function of bacteria and their effect on holobiont biology. Taken together, we provide important foundation data to extend Aiptasia as a coral model for bacterial functional studies.